The Chandra ACIS Survey of M33 (ChAseM33): Transient X-ray sources discovered in M33 - Williams, Benjamin F.; Gaetz, Terrance J.; Haberl, Frank; Pietsch, Wolfgang; Shporer, Avi; Ghavamian, Parviz; Plucinsky, Paul P.; Mazeh, Tsevi; Sasaki, Manami; Pannuti, Thomas (Astrophysical Journal, 2008)
The Chandra ACIS Survey of M33 (ChASeM33) has acquired seven fields of ACIS data covering M33 with 200 ks of exposure in each field. A catalog from the first 10 months of data, along with archival Chandra observations dating back to the year 2000, is currently available. We have searched these data for transient sources that are measured to have a 0.35-8.0 keV unabsorbed luminosity of at least 4 x 10(35) ergs s(-1) in one epoch and are not detected in another epoch. This set of the survey data has yielded seven such sources, including one previously known supersoft source. We analyzed XMM-Newton data from the archive distributed over the years 2000-2003 to search for recurrent outbursts and to get a spectrum for the supersoft transient. We find only one recurrent transient in our sample. The X-ray spectra, light curves, and optical counterpart candidates of two of the other sources suggest that they are high-mass X-ray binaries. Archival Spitzer photometry and high X-ray absorption suggest that one of the sources is a highly variable background active galactic nucleus. The other three sources are more difficult to classify. The bright transient population of M33 appears to contain a large fraction of high-mass X-ray binaries compared with the transient populations of M31 and the Galaxy, reflecting the later morphology of M33.
Keywords: binaries : close; galaxies : individual (M33); X-rays : binaries; X-rays : stars